Advances in Parvovirus Research 2020 - Gallinella, Giorgio (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Viruses of the Parvoviridae family constitute a most diverse and intriguing field of research. Parvoviruses can differ widely in their structure, genome organization and expression, virus-cell interactions, and impact on hosts. The translational implication of research on parvoviruses is relevant, since many viruses are important human and veterinary pathogens, while other viruses can be engineered as tools for oncolytic therapy or as sophisticated gene delivery vectors. Exploring the diversity and inherent complexity in the biology of these apparently simple viruses is a still challenging topic for the scientific community. The Special Issue of Viruses is a collection of recent contributions in the field of parvovirus research, encompassing many aspects of basic and translational research on viruses of the family Parvoviridae, including on their structure, replication, and gene expression in addition to virus-host interactions and the development of vaccines and viral vectors.